WHATSAPP CONTRIBUTIONS IN SPANISH TEACHING: A PERSPECTIVE OF MEANINGFUL AND COLLABORATIVE LEARNING - Iandra Maria Weirich da Silva Coelho; Márcio Luiz Oliveira Pinheiro (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
This article describes a didactic proposal, mediated by the use of WhatsApp as a potential tool for the teaching of Spanish as an additional language. Activities are drawn from collaborative and meaningful practice with authentic situations of the language usage, taking by reference the theoretical construct of the Theory of Meaningful Learning (AUSUBEL, 2003) and Collaborative Practice of Writing. The results identify positive contributions about the increased interest and motivation of students, promotion of discursive competence, interactivity, autonomy, about actions involving the authorship and collaborative construction in information network for knowledge sharing.